Two splicing variants of a new inhibitor of apoptosis gene with different biological properties and tissue distribution pattern. - Ashhab, Y; Alian, A; Polliack, A; Panet, A; Ben Yehuda, D (My University, 2001)
Using homology searches, we identified a novel human inhibitor of apoptosis (IAP) gene. This gene has two splicing variants that contain open reading frames of 298 and 280 amino acids and both contained a single copy of baculovirus IAP repeat (BIR) and RING domain. We refer here to the longer and shorter variants as Livin alpha and beta, respectively. Semiquantitative reverse transcriptase-polymerase chain reaction demonstrated a tissue-specific and non-correlated expression pattern in both adult and fetal tissues. Both mRNA variants were detected in various transformed cell lines. Despite their very close similarity, the two isoforms have different antiapoptotic properties. Both isoforms have a significant antiapoptotic activity in the Jurkat T cell line after triggering apoptosis via tumor necrosis factor and CD95 receptors. The Livin alpha but not beta protects cells from apoptosis induced by staurosporine, but in contrast, apoptosis initiated by etoposide was blocked only by the beta isoform. This difference in biological activities may indicate the presence of critical amino acids outside the BIR and RING domains. These functional and tissue distribution differences of Livin alpha and beta suggest that Livin may play a complex role in the regulation of apoptosis.